2016
DOI: 10.3892/mmr.2016.5658
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine enhances bortezomib treatment in RPMI 8226 multiple myeloma cells

Abstract: The present study investigated the interactions between decitabine (DAC) and bortezomib (BTZ) in RPMI 8226 multiple myeloma (MM) cells. Cells were exposed to DAC alone and in combination with BTZ for 48 h. A Cell Counting Kit‑8 assay was performed to assess the rate of proliferation inhibition in the cells. Cell apoptosis was investigated by Annexin V-fluorescein isothiocyanate and propidium iodide staining. Flow cytometry was used to detect the different cell cycle stages. Western blotting was performed to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Recent research showed that decitabine enhanced the effect of bortezomib in an MM cell line (29). Decitabine, combined with quisinostat, a histone deacetylase inhibitor, showed increased antimyeloma effects and altered immune cell constitution, such as increased dendritic cells and naive T cells, in a mouse myeloma model (30). Another study indicated that decitabine-mediated apoptosis in MM can be enhanced by combination with histone deacetylase inhibitor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that decitabine enhanced the effect of bortezomib in an MM cell line (29). Decitabine, combined with quisinostat, a histone deacetylase inhibitor, showed increased antimyeloma effects and altered immune cell constitution, such as increased dendritic cells and naive T cells, in a mouse myeloma model (30). Another study indicated that decitabine-mediated apoptosis in MM can be enhanced by combination with histone deacetylase inhibitor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that decitabine enhanced the effect of bortezomib in an MM cell line (29). Decitabine, combined with quisinostat, a histone deacetylase inhibitor, showed increased anti-myeloma effects and altered immune cell constitution, such as increased dendritic cells and naive T cells, in a mouse myeloma model (30). Another study indicated that decitabine-mediated apoptosis in MM can be enhanced by combination with histone deacetylase inhibitor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation at prognostically significant, differentially methylated regions (pd‐DMR) genes can significantly reduce the responses to anti‐myeloma therapy and perturb the interactions of the myeloma cells with the MM immune microenvironment, and demethylating agent decitabine can effectively reduce the methylation of pd‐DMR genes 9 . Furthermore, decitabine can not only synergistically enhance myeloma cell sensitivity to bortezomib, but also deplete myeloid‐derived suppressor cells (MDSCs) in the MM microenvironment, 10–12 while MDSCs are essential for myeloma cell survival and immune escape in the MM microenvironment 8 . To sum up, we believe that adding decitabine to currently available and affordable anti‐myeloma therapies would be very likely to develop novel and highly cost‐effective strategies for RRMM after first relapse.…”
Section: Characteristic Valuementioning
confidence: 99%